Peritonsillar abscess. Review of 89 patients - D. Manrique, Rúben (2008)
Objectives: To review the c/inical and therapeutic aspects of thecases of peritonsillar abscess observed during the last 13 years atour inpatient department.Patients and methods: Retrospective, transversal study of casesmanaged at the Department of Otorhinolaryngology at the Complejo Hospitalario Universitario de Vigo" (University Hospital ofVigo) from 1994 to 2006. Data was assessed for the 89 patientsdiagnosed with peritonsillar abscess, confirmed by fine needle aspiration.Results: Age distribution of patients showed that 83.3% of themwere 20-40 years-old. Male/female ratio was 1.211. The averagetime from the beginning of symptoms was 7.8 days and the mostfrequent symptoms were: sare throat (92. 7 %), fever (51. 7%) and trismus (50. 6%). Antibiotics were administered to 75.3% of patients before admission. Leucocytosis was present in 75.3% of cases, and left-shift (band forms excess) in 66.3%. Staphylococcus aureus was found in 26. 7% of cultured samples. The abscess was drained in 58.4% of cases. Average length of stay at the hospital was 4.5 days and there were no deaths.Conclusions: Peritonsillar abscess is an unfrequent entity in ENTinpatient departments, since majority of cases are managed ambulatorily. Fine-needle aspiration, antibiotic therapy and analgesic constitute the gold-standard for diagnosis and management.